Relative stability enhancement for brushed DC motor using a PLL interfaced with LabVIEW - Mostafa Mahmoud; Ahmed El-Biomey; El-sayed Soliman Ahmed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This work presents a fast response and stable computer based a brushed DC motor speed controller.  The controller configured of gate drive circuits for H-Bridge accompanied with data acquisition unit DAQ-6211. These gate drive circuits include, phase comparator, current booster and wave forms cleaning circuits.  An optical encoder is used for motor speed to frequency conversion. The CD4046 PLL chip compares phases of the encoder output frequency (motor speed) with a reference frequency (desired speed). The obtained phase difference (error) is used to allocate the suitable PWM duty cycles.  An H-Bridge BJT switches driven by PWM is interfaced with the motor. The system hardware is provided with a simple and accurate data acquisition unit DAQ-6211 to be interfaced with the LabVIEW software Package. This allows monitoring and storing the different measured data of this platform. The system relative stability is determined and examined based on the Bode plot analysis and design. Then the relative stability criterion (Phase Margin) is measured the closed-loop stability of the system. This system considers the fast feedback response with indication of its stability state as well as the stable wide dynamic range. It compensates the changes in system parameters due to the environmental effects and other disturbances.